Cortical somatosensory evoked high-frequency (600 Hz) oscillations predict absence of severe hypoxic encephalopathy after resuscitation. Issue 7 (July 2016) - Endisch, Christian; Waterstraat, Gunnar; Storm, Christian; Ploner, Christoph J.; Curio, Gabriel; Leithner, Christoph
Highlights: We studied cortical somatosensory evoked high-frequency oscillations (HFO) after resuscitation. Cortical HFO burst amplitudes above 70 nV largely excluded severe hypoxic encephalopathy. Analysis of high-frequency SSEP components may improve prognostication after cardiac arrest. Abstract: Objective: Following cardiac arrest (CA), hypoxic encephalopathy (HE) frequently occurs and hence reliable neuroprognostication is crucial to decide on the extent of intensive care. Several investigations predict severe HE leading to persistent unresponsive wakefulness or death, with high specificity. Only few studies attempted to predict absence of severe HE. Cortical somatosensory evoked high-frequency (600 Hz) oscillation (HFO) bursts indicate the presence of highly synchronized spiking activity in the primary somatosensory cortex. Since global neuronal damage characterizes severe HE preserved cortical HFOs may early exclude severe HE. Methods: We determined amplitudes of early and late HFO bursts in 302 comatose CA patients after median nerve somatosensory evoked potential (SSEPs) and clinical outcome upon intensive care unit discharge using the cerebral performance category (CPC) scale. Results: We detected significant early HFO bursts in 146 patients and late HFO bursts in 95 patients. Only one of 27 unresponsive wakefulness patients had a late HFO burst amplitude above 70 nV and all seventeen patients who died despite higher amplitudes died from non-neurological causes. Conclusions: High-frequency SSEP components can reliably be studied in comatose CA patients using standard equipment. Significance: Late HFO burst amplitudes above 70 nV largely exclude severe HE incompatible with regaining consciousness.